Cluster creativi per i beni culturali L'esperienza toscana delle tecnologie per la conservazione e la valorizzazione - Lazzeretti, Luciana (Strumenti per la didattica e la ricerca, 2012)
The volume analyses the contribution made by companies, institutions and research bodies operating in the region of Tuscany for the development of new technologies in the field of cultural heritage. The aim is to contribute to the current debate on the innovative capacity of artistic heritage and on cities of art, understood as creative environments characterised by the presence of clusters that are capable of generating and developing heritage-driven innovations. Through the analysis of research projects and innovation networks, the studies contained in the volume investigate the instance of laser technologies for restoration and of new ICT technologies for the digitisation of cultural heritage. The volume stems from a three-year collaboration with the "Nello Carrara" Institute of Applied Physics of the CNR of Florence.